Sports psychiatric examination in competitive sports - Gonzalez Hofmann, C.; Wyssen, A.; Schorb, A.; Allroggen, M.; Dallmann, P.; Schmidt, R. E.; Graffius, S.-T.; Niebauer, J.; Herfert, J.; Fröhlich, S.; Scherr, J.; Claussen, M. C. (Deutsche Zeitschrift für Sportmedizin, 2021)
Pre-Participation Examination (PPE) is recommended in many countries prior to or during the practice of competitive sports. The dedicated exploration of psychological complaints and illnesses in the sense of a psychiatric basic assessment within the PPE is not yet the rule.